Gender and age differences in the prevalence of different types of aggression and victimization in Spanish adolescents. - Rodríguez-Naranjo, María Carmen; Caño-González, Antonio (My University, 2023)
Aggressive behaviours are currently an important social problem, especially in childhood and adolescence. This study examined the prevalence of different types of interpersonal aggression in a sample of Spanish adolescents. Students from six secondary schools (aged 12-17 years) completed self-report and peer-report forms of the Children's Social Behaviour Scale (Crick & Grotpeter, 1995) and the Children's Social Experiences Questionnaire (Crick & Bigbee, 1998; Crick & Grotpeter, 1996). The prevalence of adolescents classified as aggressors, victims and aggressor-victims was analysed according to the frequency of different types of interpersonal violence (overt and relational/indirect), and according to gender and age. Significant differences were found with respect to role involvement, gender and forms of aggression. Age only reached significance when analyses were conducted separately for boys and girls. In summary, the results of this study reveal that approximately 2 out of 10 secondary and high school students are involved in school aggression, which means that the prevalence of aggression in Spanish adolescents is lower than that found in other countries, but still significant. By distinguishing between different types of interpersonal violence in adolescents, these findings contribute to the development of specific strategies aimed at reducing aggressive behaviour in this age group.
Keywords: Agresividad (Psicología); Adolescentes - Psicología; Adolescence; Aggression; Prevalence; Victimization